Mechanical Properties and Internal Microstructure of Concrete Brick with Addition of Effective Microorganisms - MEOR HAMZAH, MEOR MUHAMAD FITRI; ISMAIL, NOORLI (Recent Trends in Civil Engineering and Built Environment, 2021)
Effective Microorganisms (EM) technology is rapidly evolving, with applications in a wide range of sectors. However, the use of EM as an additive in concrete bricks is still in its early stages, and the microstructure image of EM containing concrete brick specimens must be assessed. As a result, study into the effects of admixing EM in concrete bricks is necessary in relation to the influence on concrete bricks performance. EM dilution is necessary to construct the EM concrete brick, EM dilution are made of 10% of EM No.1, mixed with 2% of molasses and diluted into distilled water which consists 88% of total mixture. In this study, three (3) proportions EM dilutions which is 5%, 10%, and 15% of the total mixing were added to the concrete bricks, along with a control concrete specimen without EM. All specimens are curing for seven (7) and twenty-eight (28) days before being tested for compressive strength. The analysis indicates with addition of 10% EM dilution as the optimal amount in concrete. This is shown by the increased of compressive strength of the 10% EM concrete bricks compared to control concrete brick specimen by 13.9%. Scanning Electron Microscope (SEM) micrograph examined the concrete brick 10% of EM dilution is denser and less void compared to the others brick. Based on X-Ray Diffraction was showing that 10% EM concrete brick consist the higher proportions of Portlandite , Calcite  and Silicon Oxide  compared to other specimens. It can be concluded that the optimum proportion of EM dilution can be added in concrete brick is 10% EM dilution.